Characterization Of Local Garlic (Allium sativum L.) In North Central Timor Regency Based On Phenotypic And Genotypic Characters - Polikarpia Wilhelmina Bani; Bernadina Metboki (University of Brawijaya, 2021)
Phenotypic and genotypic characters a source of superior character in the framework of plant breeding programs, especially in increasing local food yields and productivity. In this study, local cultivars of garlic from Eban, North Central Timor (TTU) were used. A total of 15 phenotypic characters were observed, and threeISSR primers were used to identify the phenotypic and genotypic characters. The phenotype characterization showed the similarities in most of the characters observed. The tuber characters showed some differences in tuber diameter (2.5 cm and 1.9 cm), the number of cloves (14 and 10 cloves), tuber weight (11.28 g and 5.18 g), weight of cloves (0.89 g and 0.45 g) for local garlic from Saenam and Fatuneno, respectively. A total of ninepolymorphic bands and 17 monomorphic bands from threeprimers Inter Simple Sequence Repeat (ISSR) were detected. The coefficient of similarity of two groups based on genotypic characters was 0.65% - 1%. This study concluded that the two local Eban garlic varieties were different based on morphology and ISSR data.Â However, phenotypically there were differences in the size of the tubers and cloves, the number of cloves per tuber, and the weight of the cloves.